(untitled) - Joint FAO/WHO Codex Alimentarius Commission (Rome, 2005)
Official and officially recognized inspection and certification systems are fundamentally important and very widely used means of food control systems. The confidence of consumers in the quality (including safety) of their food supply depends in part on their perception as to the effectiveness of these systems as food control measures. A substantial part of the worldwide trade in food, for example in meat and meat products, depends on the use of inspection and certification systems. Following the FAO/WHO Conference on Food Standards, Chemicals in Food and Food Trade in March 1991, the Codex Alimentarius Commission undertook the development of guidance documents for governments and other interested parties on Food Import and Export Inspection and Certification Systems.
Keywords: Food,Lương thực; Standards,Tiêu chuẩn